Epicardial adipose tissue volume is associated with adverse outcomes after transcatheter aortic valve replacement. (1st July 2019) - Eberhard, Matthias; Stocker, Daniel; Meyer, Martin; Kebernik, Julia; Stähli, Barbara E.; Frauenfelder, Thomas; Maisano, Francesco; Ruschitzka, Frank; Nietlispach, Fabian; Nguyen-Kim, Thi D.L.; Tanner, Felix C.
Abstract: Background: Epicardial adipose tissue (EAT) is involved in inflammation and associated with cardiovascular risk factors. It is not known whether EAT affects outcome of patients undergoing transcatheter aortic valve replacement (TAVR). Methods: 503 consecutive patients undergoing TAVR at our institution between May 2008 and November 2015 were enrolled in a prospective registry. Multi-detector computed tomography (CT) was used for EAT quantification. Outcome was assessed by 1-, 2-, and 3-year mortality and the early safety endpoint at 30 days according to the VARC-2 criteria. Results: EAT volume was larger in males than females (p = 0.003), while EAT volume indexed to BSA was similar in both genders (p = 0.348). There was a weak correlation of EAT volume with body mass index (BMI; r = 0.24; p < 0.001) and body surface area (BSA; r = 0.26; p < 0.001). Patients with larger EAT volume had an increased all-cause 1-, 2-, and 3-year mortality after TAVR in Kaplan-Meier analyses using different binary cut-off values of 100 mm 3 (log-rank p = 0.002; HR: 1.94, 95%CI: 1.15–3.26), 125 mm 3 (log-rank p = 0.001; HR: 1.70, 95%CI: 1.06–2.68), and 130 mm 3 (log-rank p = 0.001; HR: 1.69, 95%CI: 1.10–2.60). Similarly, a larger EAT volume indicated an increased risk to reach the early safety endpoint for cut-off values of 125 mm 3 (OR: 1.82; 95%CI: 1.06–3.11; p = 0.029), and 130 mm 3 (OR: 1.91; 95%CI: 1.13–3.23; p = 0.016). Indexing EAT volume did not strengthen correlation of EAT with outcome. Conclusion: EAT volume is independently associated with all-cause 1-, 2-, and 3-year mortality as well as the early safety endpoint in patients with severe aortic stenosis undergoing TAVR. Highlights: EAT volume is independently associated with all-cause mortality as well as the early safety endpoint after TAVR. There was no significant correlation between EAT volume and aortic valve calcification (Agatston Score). EAT volume quantification on pre-procedural CT may add incremental prognostic value for risk assessment of TAVR candidates.